Report on practice in industry marine fisheries. - Guzman, Reymundo M. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1963)
Fishing has become one of the major occupations not only in the Philippines but also in other major countries of the world. Fishing has brought about many methods of catching fish by modern institutions and experts. Modern fishing gears were also designed and produced to conform to the seasonal fishing in an area, and the specified species to be finished or caught. One of this modern fishing gears is the Bannuar Paanod )Ilokano name for a shrimps drift gill net) which is constructed specifically for the catching of shrimps only. This specific gear needs strong materials. Only trained fishermen should be employed in the setting of the net to insure a successful operation. In the mouths of rivers and bays, the net is drifted with the current at a desired depth decided by the operator or master fisherman including that of the time and place for hauling up the net. The condition of the fishing ground and weather condition are vital in every fishing operation and should be the concern of the whole outfit including the master fisherman. The complete operation of this gear and some other kinds are demonstrated and discussed in the forgoing report.
Keywords: Fish-Capture.